Compressive strength of concrete containing expanded polystyrene styrofoam (EPS) concrete and partial cement replacement of fly ash and silica fume / Mazizah Ezdiani Mohamad ... [et al.] - Ezdiani Mohamad, Mazizah; Ting, Robert; A Razak, Ashraf; Kifli, Azrul Zulwali; Bakie, Nisa 'Aqila; Sk Abd Razak, Sk Muiz; Rizalman, Ahmad Nurfaidhi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Expanded polystyrene (EPS) waste is generated by industry and post-consumer products. This is non-biodegradable, but is often disposed of by incineration or landfill, resulting in environmental pollution. Fly ash (FA) is a waste product from coal-fired power plants, and silica fume is a by-product of the smelting process in the production of silicon and ferrosilicon alloys. Both materials cause environmental pollution. Instead of disposing of them, there is a better way to put them to good use, such as EPS concrete (EPSC), by using EPS as a coarse aggregate and a mixture of fly ash and silica fume as a partial cement replacement. In this study, different mixes were investigated in which 100% of the coarse aggregate was replaced by EPS beads and the cement was replaced by a mixture of FA and SF at 20%, 25%, and 30%. Several laboratory tests were performed, including a slump test, a density test, a compressive strength test, and an ultrasonic pulse velocity (UPV) test.